2014
DOI: 10.1038/srep05659
|View full text |Cite
|
Sign up to set email alerts
|

A genetic epidemiology approach to cyber-security

Abstract: While much attention has been paid to the vulnerability of computer networks to node and link failure, there is limited systematic understanding of the factors that determine the likelihood that a node (computer) is compromised. We therefore collect threat log data in a university network to study the patterns of threat activity for individual hosts. We relate this information to the properties of each host as observed through network-wide scans, establishing associations between the network services a host is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Similarly, the only research using human-verified cyber attack data also found intrinsic temporal patterns [11,12]. Other patterns have also been found, including the presence of bursts or extreme values [6,9,10] and disproportionate exploitation of specific vulnerabilities [5]. Taken together, this work suggests that cyber attacks have a deterministic component: They are not fully stochastic (or random point processes).…”
supporting
confidence: 63%
“…Similarly, the only research using human-verified cyber attack data also found intrinsic temporal patterns [11,12]. Other patterns have also been found, including the presence of bursts or extreme values [6,9,10] and disproportionate exploitation of specific vulnerabilities [5]. Taken together, this work suggests that cyber attacks have a deterministic component: They are not fully stochastic (or random point processes).…”
supporting
confidence: 63%
“…the network are analyzed, instead of the contents of individual packets [40,41]. Interestingly, a quite recent study analyzing the data obtained from the host IDSs reveals strong associations between the network services running on the host and the specific types of threats to which it is susceptible [20].Making use of the plan recognition method in artificial intelligence, one can predict the attack plan from the IDS alert information [42]. Utilizing virtual or physical networks to test these IDS techniques can be costly and time consuming, hence, as an alternative, simulation modeling approaches were developed to…”
mentioning
confidence: 99%
“…Despite the prevalence of botnets and automated attacks, research has shown that there are bursty patterns and non-random exploitations of vulnerabilities, indicators of the human actors who, through expertise, demonstrate capability and intent to employ cyber attacks (Barabasi, 2005; Gil et al, 2014; Liu et al, 2015). Cyber attacks are being crafted and deployed in systematic, coordinated efforts that follow the objectives of malicious actors; effective deterrence hinges on understanding these actors (Jasper, 2015).…”
Section: Resultsmentioning
confidence: 99%